THE ASSOCIATION OF CAROTID INTIMA MEDIA THICKNESS AND THE RISK OF ISCHEMIC STROKE - Fatima Imran; Rakhshanda Jabbar; Zonia Zaman (Journal of University Medical & Dental College, 2019)
OBJECTIVES: The aim of the study was to ﬁnd the association of carotid intima media thickness and the risk of ischemic stroke.DURATION AND SETTING: This study was conducted from 15 October 2017 to 15 August 2018 in Outdoor patients Department of Radiology, Aziz Fatimah Hospital Faisalabad.SUBJECTS AND METHODS: In this Case control study, a total of 130 participants including 65 cases of stroke and 65 non-stroke controls were included. A cross sectional B-mode ultrasonography with high resolution were used to measure the intima media thickness of carotid arteries in all patients. The measurement was based upon one longitudinal image taken by high resolution ultrasound. The relationship of intima media thickness with stroke was assessed on the basis of mean value of intima media thickness in stroke patients and non-stroke controls.RESULTS: The mean age of stroke patients was 54.25 ± 8.65 years and mean age of control group was 50.45 ± 10.46 years. There were 41(63.08%) males in stroke patients and 34 (52.31%) male participants in control group. The comparison of carotid intima-media thickness signiﬁcantly (P- value< 0.001) increased in patients of stroke (0.794 ± 0.121 vs. 0.613 ± 0.099 mm) as compared to controls. The stroke patients who were also smokers had a signiﬁcantly (P-value< 0.001) higher CIMT (0.86 ± 0.19) as compared to (0.61 ± .068) smokers in control group. The CIMT in diabetic stroke patients was noted signiﬁcantly higher (0.83 ± 0.19 vs. 0.61 ± 0.07) in comparison to diabetic controls. The CIMT was found signiﬁcantly (P-value< 0.001) higher among both hypertensive stroke patients (0.87 ± 0.24) and normotensive stroke patients (0.758 ± 0.18) as compared to hypertensive controls (0.60 ± 0.11) and normotensive controls (0.58 ± 0.10).CONCLUSION: There is a signiﬁcant association of CIMT with stroke, with a signiﬁcantly higher value of CIMT among stroke patients. The risk factors like smoking, diabetes mellitus and hypertension are strong risk markers for high CIMT.